(untitled) (Bangladesh Journal of Nuclear Medicine, 2025)
Papillary thyroid carcinoma (PTC) is the most common form of thyroid cancer, typically characterized by a favorable prognosis. However, lymph node metastasis is a common feature in PTC and can complicate treatment decision and affect patient outcome. Imaging modalities such as ultrasound and CT scan are routinely used to detect lymph node involvement rather than 99mTc-petechnetate scintigraphy. This case report presents rare instance of technetium avid lymph node metastasis in a patient with PTC. The findings suggest that certain metastatic lymph nodes in PTC demonstrate technetium uptake potentially due to altered vascularity, the tissue characteristics in metastatic environment. The use of 99mTc-petechnetate imaging in PTC may provide additional diagnostic value, especially in cases with inconclusive findings from conventional imaging modalities. This case emphasizes the importance of considering a broad range of imaging techniques for accurate staging and treatment planning in patient with thyroid cancer. Further studies are needed to explore the mechanism behind technetium uptake in metastatic lymph node and to assess its prognostic significance. Bangladesh J. Nuclear Med. 27(2): 297-300, 2024